2005
DOI: 10.1002/ajmg.b.30239
|View full text |Cite
|
Sign up to set email alerts
|

Association of the putative susceptibility gene, transient receptor potential protein melastatin type 2, with bipolar disorder

Abstract: Disturbed intracellular calcium (Ca(2+)) homeostasis has been implicated in bipolar disorder (BD). Reduced mRNA levels of the transient receptor potential Ca(2+) permeable channel melastatin type 2, TRPM2, in B lymphoblast cell lines (BLCL) from bipolar I disorder (BD-I) patients showing elevated basal intracellular Ca(2+) ([Ca(2+)](B)), an index of altered intracellular Ca(2+) homeostasis, along with its location within a putative BD susceptibility locus (21q22.3), implicates the involvement of this gene in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 39 publications
(47 reference statements)
4
60
2
Order By: Relevance
“…These include cardiovascular diseases, sensory deficits, abnormal sensitivities to pain, gastrointestinal diseases, additional renal and neurodegenerative diseases, certain cancers, asthma, and even psychiatric diseases. Consistent with this last possibility is the association of alterations in TRPM2 with bipolar disorder (236,237). Finally, TRP channels are exciting targets for drug development.…”
Section: Future Perspectivesmentioning
confidence: 74%
“…These include cardiovascular diseases, sensory deficits, abnormal sensitivities to pain, gastrointestinal diseases, additional renal and neurodegenerative diseases, certain cancers, asthma, and even psychiatric diseases. Consistent with this last possibility is the association of alterations in TRPM2 with bipolar disorder (236,237). Finally, TRP channels are exciting targets for drug development.…”
Section: Future Perspectivesmentioning
confidence: 74%
“…One of the putative susceptibility loci of BD-I is associated with the chromosomal region that encodes TRPM2 (Liu et al, 2001;Xu et al, 2006Xu et al, , 2009a. SNPs in the promoter region of Trpm2 are also significantly associated with BD-I.…”
Section: +mentioning
confidence: 99%
“…PIP2 regulates the apparent affinity of the TRPM2 channel to Ca 2C31 and, to further complicate this scenario, it has been suggested that the amyloid protein can be directly incorporated into neuronal membranes and form Ca 2C -permeable ion channels (amyloid channels 32 ), which could also contribute to increases in intracellular Ca 2C and which could further activate TRPM2 and cause neurotoxicity.…”
Section: Trpv Subfamilymentioning
confidence: 99%
“…35 The TRPV3 channel is expressed in DRG, TG and spinal cord neurons as well as in cells from the skin, tongue and brain. 36 It is activated by temperatures that range between [31][32][33][34][35][36][37][38][39] C and by compounds such as camphor, thymol, carvacrol 36 and by the endogenous lipid farnesyl pyrophosphate or FPP. 37 This channel has been shown to be positively regulated by the depletion of PIP2.…”
Section: Trpv Subfamilymentioning
confidence: 99%